‘Essere, o non essere’ in scena. Sull’orma creativa di Adelaide Ristori - Megale, Teresa (Drammaturgia, 2024)
From an original perspective, this essay delves into the significance of Adelaide Ristori’s entrances and exits from the stage, the value that the Grande Attrice used to attribute to such crucial scenic moments and her expectations of national and international audiences. The actress’s creative workshop is examined here, aware of the importance of the on/off stage: a proliferation of open pieces, segments of acting that she fixes as invariable in the pages of her Studi artistici, but which she submits to continuous modifications, adjustments, changes. After broadly examining the metamorphoses of her life, this essay reflects on some interpretations (in particular, the entry of Medea and her visual source in the sculpture of Niobe) and analyses unpublished archival documents: the prospectus of the entrances and exits of Giuditta, Elisabetta and Maria Antoinetta known as the buttafuori, rather rare fragments of the so-called prove all’italiana. Ristori’s scenic protagonism is observed in the two moments, variously understood, of appearing and disappearing, of occupying the limelight or leaving it empty: a theatrical palimpsest made up of peculiar and recognisable movements, unitary and multiple at the same time, because its manifestations and declinations are multiple and unpredictable.